2018
DOI: 10.1111/pan.13514
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of propofol to dexmedetomidine for pediatric magnetic resonance imaging sedation in patients with mucopolysaccharidosis type II

Abstract: Summary Background Mucopolysaccharidosis type II patients are reported to have an elevated incidence of difficult airway. Propofol is a commonly used sedative for magnetic resonance imaging in pediatric patients, but patients who receive it may exhibit dose‐dependent upper airway obstruction and respiratory depression. Dexmedetomidine also provides adequate procedural sedation with a relatively low risk of airway obstruction. Accordingly, we introduced the use of dexmedetomidine in our practice to reduce the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Children with sleep apnoea undergoing MRI required fewer airway support interventions when dexmedetomi dine at a 2 µg kg -1 IV loading dose followed by an infusion of 2 µg kg -1 h -1 was used for sedation, in comparison to propofol [19]. Similar results -more airway problems after propofol -were reported by Kang et al [20]. In our study there was no significant difference between the respiratory events between dexmedetomidine and propofol groups, maybe due to the low dose of the drugs, especially propofol.…”
Section: Discussionsupporting
confidence: 78%
“…Children with sleep apnoea undergoing MRI required fewer airway support interventions when dexmedetomi dine at a 2 µg kg -1 IV loading dose followed by an infusion of 2 µg kg -1 h -1 was used for sedation, in comparison to propofol [19]. Similar results -more airway problems after propofol -were reported by Kang et al [20]. In our study there was no significant difference between the respiratory events between dexmedetomidine and propofol groups, maybe due to the low dose of the drugs, especially propofol.…”
Section: Discussionsupporting
confidence: 78%
“…Unlike our and other research results [ 9 , 26 ], in a previous study, Muller et al showed a more significant reduction in blood pressure in patients undergoing ERCP and concluded dexmedetomidine was associated with greater hemodynamic instability [ 27 ]. Based on the biphasic effect of dexmedetomidine on blood pressure, dexmedetomidine was used only as a single loading dose to counteract the decreased blood pressure produced by propofol during anesthesia induction in our study [ 11 , 28 ]. To overcome hypotension, a frequent side effect of dexmedetomidine, we did not infuse the dexmedetomidine continuously at a low rate during ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) is very important for early, targeted, effective and valid diagnoses and therefore the early initiation of the treatment of many diseases; however, the administration of sedative drugs, with propofol, chloral hydrate, midazolam and ketamine being amongst the most common sedative drugs used [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ], is often required for MRI to be completed, especially in the pediatric population. Nevertheless, currently available anesthetic drugs’ possible side effects, such as respiratory and/or cardiovascular depression, addiction, psychotic disorders, mutagenic effects and reductions in neurons in the limbic system, with the latter possibly leading to permanent neurological disorders, pose several limitations regarding their use [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ] and require the careful evaluation of their safety profile to select the appropriate method to monitor patients during and after the sedation procedure. Therefore, the need for research into new drugs with better safety profiles has arisen.…”
Section: Introductionmentioning
confidence: 99%